The Customized Forming of the Applied Post-Core System: Case Reports - Koray Soygun; Evrem Gülnahar; Giray Bolayır (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
The high success rate of endodontic treatments caused an increase in demand for the post-core systems in restoration of severely damaged teeth. Although metal posts are the most commonly used alternatives, the metallic color and the opaque appearance of these materials lead to discoloration of the gums and the roots. Thus, non-metal posts systems could be preferred over metal posts to be used with all-ceramic crowns. Due to their superior mechanical and biological properties, CAM/CAD fabricated zirconia post and cores can be applied inside the root canal and can be supported with ceramic crowns. Hence, the aesthetic concerns could be attended quickly and with ease. This article presents the prosthetic rehabilitation treatment of two patients with severe dentin loss, using CAD/CAM fabricated post-core and zirconia base crowns.